Postpartum Uterine Prolapse and Vaginal Cystocoele in a Murrah Buffalo - Dutt, Ravi; Niwas, Ram; Ravish, Sukhbir; Yadav, Usha; Jinagal, Sujata; Kumar, Mohit (The Indian Journal of Animal Reproduction, 2023)
A pluriparous Murrah buffalo was presented with vaginal tear over fornix vagina along with post-partum prolapse of uterus, cervix and urinary bladder. The case was managed by suturing of vaginal wall after repositioning the prolapsed mass. The catheterization of urinary bladder and modified Buhner's sutures through vulvar lips were applied to prevent the recurrence of the condition.
Keywords: Vaginal tear; Postpartum prolapse; Catheterization; Modified Buhner's sutures